American Rocket Company records - American Rocket Company; ARC Technologies; Space Enterprise Consultants; Starstruck Corporation
Correspondence, meeting minutes and notes, reports, technical papers, business plans, legal records, legislative material, financial records, printed matter, and other records relating to the commercial use of space by a private company. Documents the development of a national policy for the transition from government and military control of space to private commercial uses. Materials pertain to launch safety and insurance, government agency oversight, licensing procedures, and fair pricing systems. Includes records of several companies which preceded the American Rocket Company: Space Enterprise Consultants, ARC Technologies, and Starstruck Corporation.
First company to privately develop a rocket for commercial use, thus beginning the commercial space industry in the U.S.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aeronautics, Commercial; Aeronautics -- Safety measures; Space industrialization